IT-Based Healthy School Management at the Junior High School Level: A Literature Review - Alfiya Farashati; Supadi Supadi; Teguh Trianung Djoko Susanto (Journal of Educational Sciences, 2026)
This study reviews IT-based healthy school management at the junior high school level using a Systematic Literature Review (SLR) method guided by PRISMA 2020. From 200 articles identified (2020–2025), 20 articles met the inclusion criteria for synthesis. The analysis reveals two main clusters: the red cluster relates to students’ health literacy and information-seeking behavior (user-centered approach), while the green cluster focuses on educational technology and the role of teachers as facilitators (provider-centered approach). Developmental analysis shows a shift in focus from students’ literacy and behavior in 2022 toward infrastructure development and the role of educators in 2023–2024. The implementation of IT-based healthy school management is influenced by three key factors: human (satisfaction, skills, understanding of benefits), technology (system quality and infrastructure), and organization (policy and management support). This study affirms the importance of a holistic approach that integrates these three factors, accompanied by comprehensive training for teachers and administrators as well as improved technological infrastructure, in order to realize a healthy school ecosystem that is adaptive, responsive, and sustainable.